Measurement and Calibration of A High-Sensitivity Microwave Power Sensor with An Attenuator - Y. S. Meng (Radioengineering, 2014)
In this paper, measurement and calibration of a high-sensitivity microwave power sensor through an attenuator is performed using direct comparison transfer technique. To provide reliable results, a mathematical model previously derived using signal flow graphs together with non-touching loop rule analysis for the measurement estimate (i.e. calibration factor) and its uncertainty evaluation is comparatively investigated. The investigation is carried out through the analysis of physical measurement processes, and consistent mathematical model is observed. Later, an example of Type-N (up to 18 GHz) application is used to demonstrate its calibration and measurement capability.